PRE-REPAIR DIAGNOSTICS OF VEHICLE UNITS BASED ON TECHNICAL CONDITION - Davlatjon Mirkomilov (European Science Publishing, 2024)
This article examines the organization of pre-repair diagnostics for vehicle units, focusing on assessments based on their technical condition. By identifying and evaluating the current state of various vehicle components before repair, this approach aims to enhance the accuracy and effectiveness of maintenance efforts. The study highlights the importance of advanced diagnostic tools and methodologies in detecting potential issues early, thereby preventing more significant problems and ensuring optimal vehicle performance. Key benefits of implementing condition-based diagnostics include reduced downtime, cost savings, and prolonged vehicle lifespan. This article provides a comprehensive overview of best practices and strategies for effectively organizing pre-repair diagnostics, aligning with the evolving technical requirements of modern vehicles.
Keywords: Pre-repair diagnostics, vehicle unit assessment, technical condition evaluation, maintenance strategies, condition-based diagnostics.